Prognostic factors in ectopic Cushing's syndrome due to neuroendocrine tumors: a multicenter study. Issue 4 (April 2017) - Davi', Maria Vittoria; Cosaro, Elisa; Piacentini, Serena; Reimondo, Giuseppe; Albiger, Nora; Arnaldi, Giorgio; Faggiano, Antongiulio; Mantovani, Giovanna; Fazio, Nicola; Piovesan, Alessandro; Arvat, Emanuela; Grimaldi, Franco; et al.
Abstract : Objective: Evidence is limited regarding outcome of patients with ectopic Cushing's syndrome (ECS) due to neuroendocrine tumors (NETs). Design: We assessed the prognostic factors affecting the survival of patients with NETs and ECS. Methods: Retrospective analysis of clinicopathological features, severity of hormonal syndrome, treatments from a large cohort of patients with NETs and ECS collected from 17 Italian centers. Results: Our series included 110 patients, 58.2% female, with mean (±s.d. ) age at diagnosis of 49.5 ± 15.9 years. The main sources of ectopic ACTH were bronchial carcinoids (BC) (40.9%), occult tumors (22.7%) and pancreatic (p)NETs (15.5%). Curative surgery was performed in 56.7% (70.2% of BC, 11% of pNETs). Overall survival was significantly higher in BC compared with pNETs and occult tumors ( P = 0.033) and in G1-NETs compared with G2 and G3 ( P = 0.007). Negative predictive factors for survival were severity of hypercortisolism ( P < 0.02), hypokalemia ( P = 0.001), diabetes mellitus ( P = 0.0146) and distant metastases ( P < 0.001). Improved survival was observed in patients who underwent NET removal ( P < 0.001). Adrenalectomy improved short-term survival. Conclusions: Multiple factors affect prognosis of ECS patients: type of NET, grading, distant metastases, severity of hypercortisolism, hypokalemia and diabetes mellitus. BCs have the highest curative surgical rate and better survival compared with occult tumors and pNETs. Hypercortisolism plays a primary role in affecting outcome and quality of life; therefore, prompt and vigorous treatment of hormonal excess by NET surgery and medical therapy should be a key therapeutic goal. In refractory cases, adrenalectomy should be considered as it affects outcome positively at least in the first 2 years.